Facile preparation of highly reactive electrogenerated zinc - Abdul Jalil, Aishah; Kurono, Nobuhita; Takasugi, Shingo; Tokuda, Masao (2004)
Highly reactive electrogenerated zinc metal (EGZn/Naph) was readily prepared by electrolysis of a DMF solution containing naphthalene and a supporting electrolyte in a one-compartment cell fitted with a platinum cathode and a zinc anode. The reactivity of this EGZn/Nagh was elucidated by an efficient transformation of ethyl 2-bromobutanoate as a model substrate into the corresponding organozinc compound, which can not be achieved by the use of usual zinc metal. It was found that the electrolysis at -10 C at a constant current of 60 mA/cm2 under nitrogen atmosphere was the optimum conditions in preparing this EGZn/Naph.